Functionality and 25-hydroxyvitamin D levels in institutionalized older adults - Sarah de Jesus Francisco (Geriatrics, Gerontology and Aging, 2023)
Objectives: To evaluate the frequency of hypovitaminosis D among older adults and its association with the level of functionality. Methods: This cross-sectional observational study of older adults residing in a non-profit longterm care facility assessed functionality with the Katz Index of Independence in Activities of Daily Living. Vitamin D levels were classified as: deficient (< 20 ng/mL), insufficient (21–29 ng/mL), or normal (≥ 30 ng/mL). We used the chi-square test and Student’s t-test to compare dichotomous and continuous variables, respectively. Analysis of variance with Tukey’s post hoc test was used to assess differences between groups. Results: The sample consisted of 63 individuals whose mean age was 81 (61–113) years: 36 (55.4%) women and 27 (44.6%) men. The mean vitamin D level was 18.6 ng/mL, being < 30 ng/mL in 84.1%. The level was normal in 10 (15.9%), insufficient in 17 (27%), and deficient in 36 (57.1%). Vitamin D deficiency was present in 76.5% of those with total functional dependence (Katz = 5–6). Conclusions: We observed a high frequency of hypovitaminosis D, especially vitamin D deficiency, which was very common among those with significant functional dependence.